Postmodernism in the Theory of History: The Rhetorical Tradition and Hayden White’s Theory of the Historiographical Style - Norkus, Zenonas (Problemos, 1996)
The Postmodernist movement in the contemporary humanities is qualified as the third episode in the history of rivalry of the two Western cultural traditions – the rhetorical one (expressing what B. Pascal has called esprit de l’finesse) and the philosophical one (expressing esprit de la geometrie). The first episode of this confrontation took place in the antiquity and the second one in the Renaissance. While the mainstream of postmodernist theory is in contact with the classical rhetorical tradition only indirectly, basing itself on the structuralist and poststructuralist theory of literature, H. White’s postmodernist theory of historiography borrows directly from this tradition. Because of the ancient tradition of conceiving the historiography as a special application of the art of rhetoric, H. White’s theory can be interpreted as the restoration of the rhetorical Historik (theory of historiography). H. White, however, accepts not the classical (“logicist”) conception of language, treating tropes as mere ornatum, but the “poetical” or “romantic’” conception, going back to G. Vico and F. Nietzsche, and acknowledging “the primacy of metaphor”. So the traditional rhetorical conception of text (going from inventio to ornatum and pronuntiatio) is turned over and the topics are transformed into the tropics. H. White’s promotion of irony to the most prominent “master trope” and the professed autoirony is considered as well taken: Because H. White’s theory is based on the metaphorical application of the traditional (“logicist”) concepts of metaphor and other tropes, it deserves irony and autoirony very much. The autoironic (and by the same non-serious, playful) relativism of H. White is considered as representative for postmodernism, as neorhetoric and neosophistry of the established modern Western humanitarian academic mandarins, and as distinguished from the “serious” classical relativism legitimating Machiavellian attitudes in practical public life.